The Impact that Human Resources Have on the Products Quality in a Glass Manufacturing Company: Case Study - Marcin Olkiewicz (Communications of International Proceedings, 2021)
This publication aims to assess the employees’ impact on the production process quality and a prepared product, on the example of a manufacturing company. The research, among other things, showed that from the point of view of the production process, the most important achievements include: better identification of processes (46% of respondents), increased employee involvement (38%), increased work efficiency and profitability of the organization (40%) and a reduction in the number of accidents at work (28% of the respondent). The subject of the research was an industrial enterprise operating in the glass industry in Poland. The conducted research allowed for assessing the 100 employee’s impact on the quality in the surveyed company from the glass industry. Two hypotheses were made for the purposes of the research. The research confirmed the H1 hypothesis illustrating that the quality management of the production process when applying the different quality management doctrines, stands on a high level in the surveyed enterprise. The H2 hypothesis was also confirmed in the research stating that in the surveyed company, assessing the employees’ awareness towards their responsibility for maintaining quality through their everyday work is also on a high level, reaching 94%.
Keywords: Quality; Process; Production; Improvement.